In vitro toxicity of Niedenzuella (Tetrapterys) multiglandulosa on bovine embryos - Valquiria Bull; Ana Carolina Leite; Ana Flávia Machado Botelho; Rayanne Henrique Santana da Silva; Eliane Beatriz Magalhães Silva; Benito Soto-Blanco; Anelise de Carvalho Nepomuceno; Álan Maia Borges; Marília Martins Melo (Ciência Animal Brasileira, 2022)
Niedenzuella (Tetrapterys) multiglandulosa, a vine plant found in Brazil, has been correlated to outbreaks of poisoning in cattle and buffaloes, generating economic losses related to the death due to heart failure, miscarriage, abortion, stillbirth, and neonatal mortality. The aim of this study was to examine the embryotoxic potential of the aqueous plant extract on in vitro bovine embryos. In vitro study was performed in five replicates of bovine embryo culture assigned in two groups: control, in vitro embryo culture medium without the aqueous plant extract; treated group, with addition of 2.7mg/mL of aqueous plant extract (10%) to the embryo culture on the sixth day of culture. Cleavage rate was evaluated at day 2 of the cell culture. Viability, hatchability and underdevelopment of blastocysts on the seventh, eighth, and ninth days (D7, D8, and D9, respectively) of culture were assessed under stereoscopic microscope. On day 7, blastocysts were submitted to TUNEL assay to determine apoptotic index. In vitro exposure of bovine embryos to of N. multiglandulosa resulted in reduced embryo development and survival, evaluated by dark cytoplasm indicating poor morphology and poor quality with marked reduction of hatchability. We observed a significant reduction of blastocyst production/number of cleaved embryos (60.6% vs 41.5%); reduction of blastocysts production/total number of matured bovine oocytes (35.1% vs 21.3%); and embryonic hatching rates (38.0% vs 10.0%). However, no effects were observed on the apoptotic rate. In conclusion, aqueous extract of N. multiglandulosa leaves reduces bovine embryo viability in vitro, suggesting possible detrimental effects on embryo development. Key words: apoptosis; blastocyst; toxic plant.